Clinical and demographic study on open fractures caused by motorcycle traffic accidents - Matos,Marcos Almeida (2014)
OBJECTIVE: To assess socio-demographic characteristics of individuals that suffered open fractures caused by motorcycle traffic accident and evaluate infection rate in search of associated risk factors. METHODS: A retrospective study comprising 81 patients with open fractures caused by motorcycle accidents was carried out. Clinic and socio-demographic features were collected from patients' records. Comparison between infected and non-infected patients was performed to find out which variables were possibly associated to this complication. RESULTS: Patients were mostly young adults (mean 32.9 years old), of the masculine gender (83.9%), single (60.5%), from the country side (40.7%), mostly presenting tibial open fractures (48.2%). Fractures type IIIA and type IIIB were the most prevalent lesions (68,8%), and soft tissue damage graded as I and II were the most frequent (64.62%). Infection was present in 23.7% of the patients and it was associated to age higher than 40 years old (p=0.011), to time delay from trauma to first surgical procedure longer than 24 hours (p=0,012), and also to soft tissue damage extent (p=0.001). CONCLUSIONS: Patients with open fractures caused by motorcycle traffic accident were mostly young single men, coming from the state capital and presented severe tibial open fractures, which 23.7% of the cases progressed to infection. Level of Evidence III, Retrospective Comparative Study.